2005
DOI: 10.1039/b414856h
|View full text |Cite
|
Sign up to set email alerts
|

A chemical method for the convenient surface functionalisation of polymers

Abstract: A method for the application of carbenes as reactive intermediates for surface modification of polymeric substrates has been developed; the efficacy of the process has been demonstrated by irreversible dyeing of polystyrene, polythene, nylon, silica, and controlled pore glass, and to a limited extent, polytetrafluoroethylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 7 publications
2
48
0
Order By: Relevance
“…We recently reported a highly novel strategy for the modification of the surface of materials, originally for the alteration of their colour, 3,4 but have subsequently shown that this approach can be applied for the introduction of biocidal 5 and fluorescence activity, 6 and biocompatibility. 7 The method relies upon the generation of carbenes by thermolytic or photolytic methods and their irreversible attachment by insertion into available surface chemical groups; a similar approach has recently been reported by Hayes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported a highly novel strategy for the modification of the surface of materials, originally for the alteration of their colour, 3,4 but have subsequently shown that this approach can be applied for the introduction of biocidal 5 and fluorescence activity, 6 and biocompatibility. 7 The method relies upon the generation of carbenes by thermolytic or photolytic methods and their irreversible attachment by insertion into available surface chemical groups; a similar approach has recently been reported by Hayes.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work had indicated that methoxy-activated ring systems produced lower colour intensity than more reactive amino groups in similar polymer modifications. 4 In order to gain some information relating to the thickness of the introduced layer, ellipsometry measurements on silicon modified with diaryldiazo compound 5 were made (Scheme 1). The results suggested a layer thickness of 6.3 ± 0.1 nm; assuming that the introduced organic residues are approximately orthogonal to the silicon surface with a height of some 0.75 nm, this gives a layer of about nine molecules high.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we have shown that the application of external pressure to the region of adhesive contact results in the increase in the van der Waals forces (van der Waals adhesional pressure), according to equation (15). In particular, if excessive electric charge is present at the polymer-fiber interface, then not only an additional Coulombic component of the adhesional pressure appears, but also the molecular adhesion component increases.…”
Section: S Zhandarov and E Mädermentioning
confidence: 92%
“…Then, the increase in the molecular component of the adhesive pressure was determined directly from equation (15). The calculated p E and δp m values for the studied polymer-fiber systems are shown in another technique for interfacial bond strength measurement, namely, the single fiber composite (fragmentation) test [49 -51].…”
Section: Non-polar Polymersmentioning
confidence: 99%
“…In one approach, by exploiting the well-known reactivity of carbenes with both and chemical bonds for insertion and addition processes respectively, the functionalization of both reactive (organic and inorganic polymers) and inert (diamond, nanotubes, hydrocarbon polymers) materials using diaryldiazomethanes 1 to introduce varied surface properties, [2][3][4] including chromophoric, 5 protein a±nity, 6,7 biocidal, 8 chelation, 9 biocompatibility, 10 payload delivery, 11 dispersability, 12 nano¯lling, 13 and wettability 14,15 e®ects has been achieved. Of interest, however, was whether the surface loading density which could be achieved using this approach, which was generally in the range 0.01-0.2 mmol/g, [2][3][4] was su±cient to permit the reversible binding of small molecules at a level which was both detectable and had the capacity for a therapeutic e®ect; that this might be possible which was suggested from earlier work in which the binding of hydrogen peroxide was shown to lead to bactericidal properties, a result which was considered likely to be a best case scenario, since the existence of an extensive hydrogen binding network appeared to support multiple hydrogen peroxide units per unit of introduced surface urea groups giving high overall surface loading. 8 The development of drug delivery systems, and in particular the surface delivery of bioactive agents, especially from nanoparticles, [16][17][18][19][20][21] is currently of interest for its obvious medical and hygiene applications [22][23][24] especially in the area of antibacterials 25 ; recent work is noteworthy in that regard.…”
mentioning
confidence: 99%